Portuguese Higher Education System and Bologna Process Implementation - David, Fátima (2018)
This research aims to analyze the grown of the Portuguese higher education system, as well as the courses diversification, after the implementation of the Bologna Process in 2006. On the one hand, the Constitution of the Portuguese Republic of April 2, 1976, gives to all citizens a right to equal opportunities for school success and to access to the higher education. On the other hand, the Bologna Process aims to construct a European higher education area that establishes comparability, compatibility and coherence between the higher education system through the harmonization of academic degrees and the guarantee of quality in all the European institutions. Thus, methodologically, this research relied on a two-track approach. The first approach takes the form of a literature review, based in the legal regime of Portuguese and European higher education system. The second approach takes the form of an empirical research based on a descriptive statistical analysis, supported on the statistical information provided by Portuguese Ministry of Education and Science that shows the increases of the Portuguese’ qualifications and the courses diversification, after the implementation of the Bologna Process in 2006. Indeed, the research provides empirical evidence about the Portuguese higher education institutions engagement in the Bologna process.